2013
DOI: 10.1097/ftd.0b013e318282c3a6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Azathioprine Dosage and Thiopurine Metabolites in Pediatric IBD Patients

Abstract: The reliable AZA dose-metabolites relationship is useful for clinicians to guide the dosing regimen to maximize clinical response and minimize side effects or to consider alternative therapies when patients have preferential production of the toxic 6-MeMPN. These results may be of potential interest for optimizing thiopurine therapy to achieve safe and efficacious AZA use in pediatric IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Only patients with a stable dose of AZA for at least 2 months before measurements of laboratory parameters and clinical records were included to ensure equilibration of treatment . Samples from patients with evidence of poor compliance confirmed by clinicians with total nucleotide levels (6‐TGN + 6‐MeMPN) below 150 pmol/8 × 10 8 RBCs were excluded . Likewise, patients who had received blood transfusions within 3 months were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Only patients with a stable dose of AZA for at least 2 months before measurements of laboratory parameters and clinical records were included to ensure equilibration of treatment . Samples from patients with evidence of poor compliance confirmed by clinicians with total nucleotide levels (6‐TGN + 6‐MeMPN) below 150 pmol/8 × 10 8 RBCs were excluded . Likewise, patients who had received blood transfusions within 3 months were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Thiopurine use is associated with dose-dependent adverse drug reactions (ADRs), often leading to dose reduction or drug discontinuation [9]. Hematological toxicity in the form of myelosuppression, secondary to either thiopurine or elevated levels of its metabolite 6-thioguanine (6-TGN), is the most serious ADR.…”
Section: Introductionmentioning
confidence: 99%
“…4,15,17,23 In accordance with the conclusion by Osterman et al 16 in a meta-analysis, this study found that higher 6-TGN levels were associated with therapeutic response. Furthermore, the wide interindividual variability in thiopurine metabolism observed in previous studies 14,20,28,30,31 supports the need of treatment individualization based on the metabolite monitoring in clinical settings. Routine testing of metabolites to guide dosing is likely to be promising; yet, conclusion from well-designed prospective studies is still needed.…”
Section: Discussionmentioning
confidence: 63%
“…Because infliximab has been shown to influence metabolite levels 20,21 and an introduction of infliximab during the AZA therapy was part of the criteria for nontherapeutic response to AZA, samples corresponding to the concomitant use of infliximab were also excluded. Measurements of metabolite levels performed after at least 2 months of a stable dose of AZA were included to ensure equilibration of metabolite levels.…”
Section: Data Collectionmentioning
confidence: 99%